An epidemiological investigation of the prevalence of digestive diseases in the older prisoner population in Taiwan - Zhu Liduzi Jiesisibieke; Ping Tao; Yen-Chun Wang; Ching-Wen Chien; Tao-Hsin Tung (Journal of Health, Population and Nutrition)
Abstract Objective The prison population has been increasing globally, and prisoner health is an important issue of global health. However, it has not received sufficient attention, especially in developing countries and regions. Among all the prisoners, the health status of older prisoners requires special attention due to their declining health and energy. This study aims to assess the prevalence of digestive diseases among older prisoners in Taiwan. Methods Data on older prisoners from the National Health Insurance Research Database from January 1 to December 31, 2013, were used in this study. Digestive diseases were assessed in 2,215 older prisoners using the International Classification of Diseases, 9th revision Clinical Modification (ICD-9-CM). We identified the most common digestive diseases and explored any sex-specific differences in their prevalence. Results The estimated prevalence of digestive system diseases among the prisoners was 51.56%. Older women prisoners had a higher prevalence (62.68%) compared to men prisoners in general (50.80%). Diseases with a prevalence > 10% include esophageal, gastric, and duodenal diseases; diseases of the oral cavity, salivary glands, and jaws; and other intestinal and peritoneal diseases. Women prisoners showed a significantly higher prevalence of diseases of the oral cavity, salivary glands, jaws, esophagus, stomach, duodenum, non-infectious enteritis, and colitis. Conclusion Our findings indicate that a considerable number of older prisoners in Taiwan experienced digestive diseases, which may be attributable to general deterioration of physical function and poor resistance. Early detection and treatment are crucial for these conditions, and it is important to maintain human rights and justice in prison systems.